Distal middle cerebral artery aneurysm manifestation against the background of COVID-19 - D. V. Litvinenko; E. A. Litvinenko; V. V. Tkachev; G. G. Muzlaev (Сеченовский вестник, 2022)
A significant part of distal cerebral aneurysms belongs to the category of complex. Traditional methods of shutting down such aneurysms are not applicable. Treatment tactics remain a subject of debate. The presence of COVID-19 complicates the course of the disease and complicates the routing of the patient to a specialized hospital.Description of the case. A 36-year-old man with COVID-19 developed an ischemic stroke in the territory of the right middle cerebral artery (MСA), clinically manifested by dysarthria and pronounced left-sided hemiparesis. Cerebral angiography (CAG) revealed thrombosis of the parietal branch of the M2 segment of the right MСA with distal filling of the channel from the territory of the left MСA. After 3 months, according to the control CAG, recanalization of the M2 segment of the right MСA and fusiform aneurysm of this segment of the artery were diagnosed. To turn off the aneurysm, an intra-intracranial anastomosis was applied between the upper and lower M2 segments of the right MСA and an extra-intracranial anastomosis between the parietal branch of the right superficial temporal artery and the cortical branch from the territory of the compromised M3 segment of the MСA, the aneurysm was excised. The postoperative period was complicated by reinfection of SARS-CoV-2. After the treatment, the patient was discharged in a satisfactory condition without neurological deficit.Discussion. Resection of an aneurysm with revascularization of the distal bed can be considered as the method of choice in patients with distal aneurysms if it is impossible to apply traditional clipping. The presence of COVID-19 infection increases the risk of thrombotic complications, imposes increased requirements on the technique of performing vascular anastomoses.